Dissociation and the Unconscious Mind: Nineteenth-Century Perspectives on Mediumship - Alvarado, Carlos S. (Journal of Scientific Exploration, 2020)
There is a long history of discussions of mediumship as related to dissociation and the unconscious mind during the Nineteenth Century. After an overview of relevant ideas and observations from the mesmeric, hypnosis, and spiritualistic literatures, I focus on the writings of Jules Baillarger, Alfred Binet, Paul Blocq, Théodore Flournoy, Jules Héricourt, William James, Pierre Janet, Ambroise August Liébeault, Frederic W.H. Myers, Julian Ochorowicz, Charles Richet, Hippolyte Taine, Paul Tascher, and Edouard von Hartmann. While some of their ideas reduced mediumship solely to intra-psychic processes, others considered as well veridical phenomena. The speculations of these individuals, involving personation, and different memory states, were part of a general interest in the unconscious mind, and in automatisms, hysteria, and hypnosis during the period in question. Similar ideas continued into the Twentieth Century.